Bibliometric analysis of nanoparticle research for diagnostics and therapeutics in hepatocellular carcinoma - Xiaoqing Li; Yue Li; Jingyan Zhu; Yang Yang; Shipeng Yang (Discover Nano)
Abstract Objectives The aim of this study was to explore the bibliometric analysis of nanomaterials-based therapies for hepatocellular carcinoma as a means of assessing the current state of development and future trends in the field. Materials and methods Literature on hepatocellular carcinoma and nanomedicine interactions was searched from the core database of the Web of Science and bibliometric and visualisation analyses were performed using VOSviewer, CiteSpace and GraphPad Prism data analysis software. We focused on important keywords, countries, authors, affiliations, journals, and literature in the field of nanomaterials for HCC. Results The search resulted in the finalization of 421 documents. The search resulted in the finalization of 421 documents. From 2008 to 2023, nanomedicine research in HCC has developed rapidly, and the number of published papers has steadily increased, increasing by about 2300%. There are currently 57 countries involved in research in this area. Among them, The USA had the strongest international cooperation network and cooperated most closely with China. Gene delivery and carbon nanotubes were early keywords, immunotherapy and nanocarriers are recent research hotspots. It is important that the selection of nanocarriers and drug delivery have become the core trends driving the development of hepatocellular carcinoma. Conclusion The combination of nanomaterials with traditional imaging techniques such as MRI can improve the early diagnosis rate of HCC. Nanomaterials can achieve precise targeting of cancer cells by encapsulating drugs, loading bioactive molecules or modifying specific targeting ligands, thus significantly improving drug efficacy and effectively reducing adverse reactions in therapy.